2023
DOI: 10.3389/fmicb.2023.1083330
|View full text |Cite
|
Sign up to set email alerts
|

Amoxicillin-docosahexaenoic acid encapsulated chitosan-alginate nanoparticles as a delivery system with enhanced biocidal activities against Helicobacter pylori and improved ulcer healing

Abstract: Encapsulation of amoxicillin (AMX) for drug delivery against Helicobacter pylori infection and aspirin-induced ulcers in rat’s stomachs was performed using docosahexaenoic acid (DHA)-loaded chitosan/alginate (CA) nanoparticles (NPs) developed by ionotropic gelation method. The physicochemical analyses of the composite NPs were performed by scanning electron microscopy, Fourier transform infrared spectroscopy, zeta potential, X-ray diffraction, and atomic force microscopy. The encapsulation efficiency of AMX wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…However, metformin can be used as an adjuvant to reduce the effective dose of AMX. We have previously reduced the effective dose of this antibiotic by encapsulation with chitosan and docosahexaenoic acid [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, metformin can be used as an adjuvant to reduce the effective dose of AMX. We have previously reduced the effective dose of this antibiotic by encapsulation with chitosan and docosahexaenoic acid [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles supplemented with 2% (v/v) DHA significantly hindered the growth of H. pylori compared to the control group (no nanoparticles added). Moreover, the inclusion rate of antibiotics increased to 76 percent after the addition of this fatty acid ( Khoshnood et al, 2023 ). In vivo , fucus-chitosan/heparin nanoparticle delivery systems significantly increased the ability to inhibit H. pylori compared to conventional antibiotic therapy.…”
Section: Main Treatment Methodsmentioning
confidence: 99%
“… [ 110 ] Amoxicillin Oil-in-water emulsification combined with ionic gelation method In vivo Helicobacter pylori Growth inhibition rate level: AMX-loaded NPs > Blank NPs The incorporation of amoxicillin into nanoparticles enhances its antibacterial effects compared to conventional amoxicillin due to increased drug bioavailability. [ 111 ] Amoxicillin Ionotropic pre-gelation combined with polyelectrolyte complexation method Helicobacter pylori In vivo mucopenetration studies revealed that amoxicillin-loaded NPs exhibit higher percentage drugs accumulated than free amoxicillin The nanoparticle formulation helps amoxicillin in maintaining its stability during adhesion process in gastric juice environment. It also increase uptake of amoxicillin into gastric mucosa due to reduced particle size.…”
Section: Evidence Of Antibacterial Agents’ Delivery Using Chitosan/al...mentioning
confidence: 99%
“…It also increase uptake of amoxicillin into gastric mucosa due to reduced particle size. [ 119 ] Amoxicillin (AMX) combined with docosahexaenoic acid (DHA) Oil-in-water emulsification combined with ionic gelation method In vivo Helicobacter pylori Growth inhibition rate level: AMX-DHA-loaded NPs > AMX-loaded NPs > DHA-loaded NPs > Blank NPs The system is capable of loading multiple components, providing additive properties from the addition of DHA [ 111 ] Enrofloxacin Ionic gelation method In vitro and in vivo Escherichia coli MIC: Free Enrofloxacin = 1 µg/mL Enrofloxacin-loaded NPs = 0.125 µg/mL Drug delivery in the nano-system protects the drug from negative exposure, thereby indirectly increasing efficacy. [ 112 ] Doxycycline Ionotropic Gelation Method In vitro Proteus mirabilis, Escherichia coli , and Enterococcus faecalis Inhibition rate: Doxycycline-loaded NPs > Blank NPs > Free Doxycycline > Negative Control Synergistic effects arise from the nano-charge of alginate guided by non-ionic interactions between chitosan and bacterial peptidoglycan teichoic acid.…”
Section: Evidence Of Antibacterial Agents’ Delivery Using Chitosan/al...mentioning
confidence: 99%
See 1 more Smart Citation